Novel SBF1 splice‐site null mutation broadens the clinical spectrum of Charcot‐Marie‐Tooth type 4B3 disease. Issue 5 (9th August 2018) - Flusser, H.; Halperin, D.; Kadir, R.; Shorer, Z.; Shelef, I.; Birk, O.S.
Abstract : Four siblings of consanguineous Bedouin kindred presented at infancy with an autosomal recessive syndrome of congenital microcephaly, facial dysmorphism, strabismus, developmental delay and ataxia with positive pyramidal signs. Toward the end of their first decade, they developed areflexia, multiple cranial neuropathies and severe polyneuropathy with progressive muscle weakness, affecting proximal and distal extremities. Physical assessment exhibited kyphoscoliosis, bilateral syndactyly and distal muscle wasting with drop‐foot and pes cavus. Magnetic resonance imaging (MRI) showed profound cerebellar atrophy with highly unique findings at the pontine and mesencephalic levels, previously described as "fork and bracket" signs. Genome‐wide linkage analysis identified a single ~1.5 Mbp disease‐associated locus on chromosome 22q13.33. Whole exome sequencing identified a single novel homozygous deleterious splice‐site mutation within this locus in SET binding factor 1 ( SBF1 ). SBF1 missense mutations were shown to underlie Charcot‐Marie‐Tooth (CMT) type 4B3 disease, a rare autosomal recessive subtype of CMT4. The novel SBF1 null mutation highlights distinct severe phenotypic manifestations, broadening the clinical spectrum of SBF1 ‐related neuropathies: cerebellar and pyramidal signs evident in the first months of life with peripheral polyneuropathy emerging only toward the end of the first decade, together with unique MRI findings. Abstract : Four siblings of a consanguineous family presented at infancy with unique manifestations of Charcot‐Marie‐Tooth (CMT) disease. Profound cerebellar atrophy with ataxia and positive pyramidal signs were the presenting symptoms along with highly unique "fork and bracket" brainstem anomalies. Through whole exome sequencing, we identified a novel homozygous splice‐site mutation within SBF1, encoding SET binding factor 1. Only four families with SBF1 mutations have been identified to date, all with CMT type 4B3. As the phenotype we describe is distinct from the classical disease delineation of CMT4B3, our data establish a new disease type with SBF1 mutations.